Risks for animal health related to the presence of zearalenone and its modified forms in feed. (31st July 2017) - ,; Knutsen, Helle‐Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hogstrand, Christer; et al.
Abstract: Zearalenone (ZEN), a mycotoxin primarily produced by Fusarium fungi, occurs predominantly in cereal grains. The European Commission asked EFSA for a scientific opinion on the risk to animal health related to ZEN and its modified forms in feed. Modified forms of ZEN occurring in feed include phase I metabolites α‐zearalenol (α‐ZEL), β‐zearalenol (β‐ZEL), α‐zearalanol (α‐ZAL), β‐zearalanol (β‐ZAL), zearalanone (ZAN) and phase II conjugates. ZEN has oestrogenic activity and the oestrogenic activity of the modified forms of ZEN differs considerably. For ZEN, the EFSA Panel on Contaminants in the Food Chain (CONTAM) established no observed adverse effect levels (NOAELs) for pig (piglets and gilts), poultry (chicken and fattening turkeys), sheep and fish (extrapolated from carp) and lowest observed effect level (LOAEL) for dogs. No reference points could be established for cattle, ducks, goats, horses, rabbits, mink and cats. For modified forms, no reference points could be established for any animal species and relative potency factors previously established from rodents by the CONTAM Panel in 2016 were used. The dietary exposure was estimated on 17, 706 analytical results with high proportions of left‐censored data (ZEN about 60%, ZAN about 70%, others close to 100%). Samples for ZEN were collected between 2001 and 2015 in 25 different European countries, whereas samples for the modified forms were collected mostly between 2013 and 2015 from three Member States. Based on exposure estimates, the risk of adverse health effects of feed containing ZEN was considered extremely low for poultry and low for sheep, dog, pig and fish. The same conclusions also apply to the sum of ZEN and its modified forms.